The linkages between trade, financial openness, and economic growth in China: An ARDL-bound test approach - Khalid Usman (Journal of Applied Economics, 2023)
This research examines the linkages between trade, financial openness, and economic growth in China from 1992 to 2021, using Granger causality analysis in the ECM model to identify the trend of a causal relationship between the variables. The results confirm the validity of export-led growth and the supply-leading hypotheses in China. Moreover, China's broad money is output-oriented, and the significance of exports to China's economy is supported by the influence of real income and imports caused by exports. Lastly, the research highlights that domestic credit expansion by the banking industry stimulates global trade growth; however, import changes cause broad money fluctuations. Policymakers can utilize these findings to identify the trend of the growth and development of the trade and financial industry of the economy, as there is substantial proof that a meaningful relationship is occurring between economic growth, trade, and the financial development sectors of the economy.
Keywords: 330; ARDL bound test; economic growth; financial development; Trade openness